Prediction of natural fracture distribution characteristics in tight oil and gas reservoirs based on paleotectonic stress field - Lin, Lifei; Wang, Mingwei; Wang, Yanwei; Gao, Yi; Li, Song (Frontiers in Energy Research, 2023)
The production of fractured oil and gas reservoirs in the world accounts for more than half of total oil and gas production and is one of the important fields for increasing oil and gas storage and production in the 21st century. The key to characterizing fractured oil and gas reservoirs is the distribution pattern of natural fractures. The distribution of natural fractures is dominated by structural deformations and fractures. Therefore, analytical and structural simulations of the tectonic stress field in geological structural systems play a crucial role in obtaining fracture distribution patterns. In this paper we have developed a description of the distribution of natural fractures based on finite element numerical simulations of the paleotectonic stress field. The study focused on the Chang 7 and Huangjialing Chang 8 reservoirs in the underground Siwan region of the Ordos Basin in China. First, an experimental assessment of the rock mechanics of the reservoir was completed, and the values of the paleotectonic stresses obtained from the tests were used as inversion criteria for the stress field simulations. Based on the geology, a refined geological model has been developed to study the structure of the Chang 7 and Chang 8 oil reservoirs in the block. The simulated paleotectonic stress fields for natural fractures in the Indosinian period are as follows: maximum principal stress of 94.67 MPa, minimum principal stress of 21.58 MPa, and vertical stress of 28.07 MPa. The direction of maximum principal stress remains essentially in the NE-SW direction, with the largest differential stress occurring in the Chang8 oil layer group in Huangjialing, while the differential stress is relatively uniform in the Chang7 oil layer group in Xiasiwan. It predicts the relative density of natural fractures in the Chang 7 and Chang 8 reservoirs, and finds high-to-low plane heterogeneity in the Huangjialing Chang 8 reservoir group and the Xiasiwan Chang 7 reservoir group, respectively.The paper reveals the pattern of development of reservoir fractures in both vertical and horizontal directions, providing an important geological basis for efficient and rational exploitation of oil and gas resources in the study area and improving oil recovery.